2023
DOI: 10.1044/2022_jslhr-22-00253
|View full text |Cite
|
Sign up to set email alerts
|

Embedding Executive Function Training Into Early Literacy Instruction for Dual Language Learners: A Pilot Study

Abstract: Purpose: Early literacy skills are key indicators of future reading development for young dual language learners (DLLs). Additionally, emerging evidence indicates that young children's executive function (EF) skills are uniquely associated with elementary school reading outcomes (Ribner et al., 2017). Therefore, the purpose of this pilot study was to evaluate the potential for embedding strategies to support EF development within evidence-based early language and literacy instruction for young DLLs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Based on the (adaptive) training on these processes, students are expected to efficiently use strategies to maintain information and to facilitate the role of long‐term memory in working memory‐demanding academic tasks, in order to acquire new academic information in a more general learning setting. Our review showed that doing such tasks results in promising effects on academic outcomes, especially for at‐risk learners (Goodrich, Peng, Bohaty, Leiva, & Thayer, 2023; Peng & Fuchs, 2017).…”
Section: Domain‐specific Approach Of Working Memory Trainingmentioning
confidence: 98%
“…Based on the (adaptive) training on these processes, students are expected to efficiently use strategies to maintain information and to facilitate the role of long‐term memory in working memory‐demanding academic tasks, in order to acquire new academic information in a more general learning setting. Our review showed that doing such tasks results in promising effects on academic outcomes, especially for at‐risk learners (Goodrich, Peng, Bohaty, Leiva, & Thayer, 2023; Peng & Fuchs, 2017).…”
Section: Domain‐specific Approach Of Working Memory Trainingmentioning
confidence: 98%